Lookup table built-up for power semiconductor module - Bhowmick, Sumit (2016)
The use of Insulated Gate Bipolar Transistors (IGBT) are very popular as switching devices in a host of different applications such as consumer electronics, appliances, medical equipment and transport technology. There are numerous characteristics that affect the functioning of IGBTs. Due to their increasing popularity of being used for high switching operations, it is crucial to monitor the IGBT’s ageing and degradation. This can help determine the lifetime of the device components and help take measures to prolong it by tracking changes in its parameters. Such monitoring will help in reducing maintenance costs and prevent damages to the machinery they are used in. Despite the increasing dependence on the use of IGBT devices, little has been done to verify its degradation behaviour, the various factors affecting their lifetime and how its characteristics change under different working and external conditions. This study aims to understand the structure and construction of an IGBT, the methods to study IGBT ageing and changes in IGBT parameters under different working conditions. A DC chopper test circuit was built to degrade IGBT modules through power cycling. Subsequently, IGBT modules were also degraded through thermal chamber cycling. A few key characteristics like resistances and power losses were measured for both good and degraded modules under different temperature conditions. These findings were used to create a sample lookup table which can help study the variation in IGBT parameters with ageing of the device. Further experiments can be done to get more results under different stressors to further enhance the design and usage of the lookup table. Moreover, other switching devices like BJTs and MOSFETs can also be studied to monitor their lifetime characteristics.